Gender Differences in Seeking Health Care and Postintervention Pain Outcomes in Foot and Ankle Orthopedic Patients - Kyla A. Petrie; Jason N. Chen; Hunter Miears; Jerry Speight Grimes; Mimi Zumwalt (Mary Ann Liebert, 2022)
Background: A significant portion of the adults suffer from foot and ankle pain. The sex differences that exist throughout health care, pain management, and orthopedics may further complicate treatment strategies. The purpose of this study was to determine if there were any differences in women and men in health care seeking behavior and symptom chronicity in a West Texas orthopedic population with foot and ankle conditions. Materials and Methods: Data from 137 patients were collected in a retrospective chart review. Data were analyzed to determine if there were sex differences in time to primary care provider (PCP) after ankle injury, referral time from PCP to orthopedic surgeon consult, time from orthopedic consult to surgical intervention (if applicable), and chronicity of symptoms. Results: Women had a significantly higher percentage of chronic injuries than men (30.7% vs. 10.9%), but there were no sex differences in time to PCP from the time of injury, time from PCP visit to orthopedic consult, and time from orthopedic consult to surgical intervention. There were also no differences in those same time frames when compared by chronicity of symptoms (acute injury vs. chronic injury). Finally, we did not find any differences in pain scores between sexes or chronicity of symptoms. Conclusions: This study suggests that conventional health seeking sex differences may not apply to the foot and ankle patient population in West Texas and surrounding rural areas. Continuing to examine patterns in sex differences may lead to the development of more efficient and tailored treatment approaches and better outcomes.